Demographics and clinical features predictive of allergic versus non-allergic rhinitis in children aged 6–18 years: A single-center experience of 1535 patients. (July 2017) - La Mantia, Ignazio; Andaloro, Claudio
Abstract: Background: Chronic rhinitis (CR) is one of the most common causes accounting for lost-school days, absenteeism and resource utilization in pediatric patients. Distinction between common causes of CR, allergic (AR)and non-allergic rhinitis (NAR), based upon clinical features is critical, especially in primary care settings or facilities with lack of allergen sensitivity testing, as management strategies differ considerably. The current study elucidates clinical factors, particularly facial features associated with AR and NAR using a large cohort. Methods: In a retrospective cohort analysis of pediatric patients aged 6–18 years, we assessed patient demographics, clinical symptoms, and signs associated with allergic rhinitis using multivariable regression techniques. Results: Overall, 1490 patients (mean age: 10.11 ± 3.31 years; 48% female; 69% AR and 31% NAR) were included in the study. In multivariable regression analysis, major clinical features associated with AR were: sneezing (OR: 3.53; 95% CI: 2.35–5.32; p < 0.001), rhinorrhea (OR: 1.77; 95% CI: 1.18–2.66; p = 0.006), nasal itching (OR: 17.88; 95% CI: 11.92–26.83; p < 0.001), horizontal nasal crease (OR: 5.09; 95% CI: 1.29–20.01; p = 0.020) and conjunctivitis (OR: 4.66; 95% CI: 3.28–6.62; p < 0.001). On the contrary, we noted presence of Dennie-Morgan fold (OR: 1.67; 95% CI: 1.11–2.56; p = 0.014), moderate to severe persistent or intermittent symptoms to be likely associated with NAR than AR. Conclusion: In pediatric patients presenting with symptoms of rhinitis, facial hallmarks serve as an adjunct to sensitivity testing in establishing a diagnosis as well as differentiating between NAR from AR, albeit individualized upon patient history and clinical features.